Integrating ex-prisoners in the local community - Fidelus, Anna H. (Forum Pedagogiczne, 2020)
This article draws attention to solutions aimed at supporting convicts after they serve their time in prison. The basic thesis, argued and confirmed is the belief that work with former prisoners should be characterized by the integration of activities of many institutions, undertaken on the basis of a society functioning in a specific social environment. In theory it can be assumed that the resocialization process carried out in a penitentiary should be effective enough for the person leaving this institution to be prepared to live in a free environment and function in accordance with social, moral and legal norms. Unfortunately, this is not always the case. The concrete evidence and statistical data indicate a significant number of persons relapsing into crime.